Willingness to pay towards the sustainability of Forest Research Institute Malaysia’s (FRIM’s) canopy walkway - Ramlan, Mohd Aswad; Radam, Alias; Yacob, Mohd Rusli; Yahya, Noor Azlin (MultiCraft Publishers, 2011)
FRIM’s canopy walkway is one of the main visitors’ attractions at the Forest Research Institute Malaysia (FRIM). It was built in 1992, initially for research purposes but later in 1993 the walkway was opened to the public for education and nature appreciation activities. Since its opening, the walkway has recorded visitation from tourists all around the globe, bringing good revenues to FRIM’s management. A study was conducted to estimate the economic value of FRIM’s canopy walkway, based on visitors’ expressing willingness to pay (WTP). The relevant values were estimated by utilizing dichotomous choice form of contingent valuation method and uses Logit and Probit models to estimate the visitor’s WTP responses for the access to the walkway. Based on the estimation results, the calculated mean of WTP ranged from MYR5.33 to MYR13.32 for the Logit model, and for the Probit model ranged from MYR5.39 to MYR13.02 based on 95 percent confidence interval. The study had shown that visitors to FRIM’s canopy walkway are willing to pay about MYR7.61 for the entrance perm it. The entrance fee collections are used as additional funds to the allocations made for the costs of maintenance and conservation of FRIM’s canopy walkway, which are quite high due to the technicality of the walkway’s structure and logistics problem to access the facility.